Implementation Of PSAP No. 11 In The Preparation Of Consolidated Financial Reports At The Secretariat Of The West Nias Regency DPRD - Daeli, Mujur Kurniawati; Zai, Kurniawan Sarototonafo; Kakisina, Sophia Molinda; Zebua, Fakta Solala (Universitas Dehasen Bengkulu, 2025)
This study aims to examine the extent to which Government Accounting Standards Statement (PSAP) No.11 has been implemented in the preparation of consolidated financial statements at the Secretariat of the DPRD of Nias Barat Regency. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results indicate that the implementation of PSAP No.11 has been fairly well executed, as evidenced by the preparation of consolidated reports such as the Budget Realization Report (LRA), Statement of Changes in Budget Surplus (LPSAL), Balance Sheet, Operational Report (LO), Cash Flow Statement (LAK), and Statement of Changes in Equity (LPE) in accordance with the standards. However, there are still obstacles, including limited human resources in understanding the technical aspects of eliminating inter-unit transactions and the suboptimal use of information systems. This shows that although the implementation of PSAP No.11 is aligned with the applicable standards, it requires capacity building for human resources and optimization of technology to support more accurate, transparent, and accountable financial reporting.